Dampak Disiplin Kerja dan Komunikasi terhadap Kepuasan Kerja (Studi pada SMA IT Fithrah Insani Bandung Barat) - Fitrianty, Aulia Gita; Prabowo, Juddy (IPM2KPE, 2024)
The purpose of the study was to examine the influence of work discipline and communication on teacher job satisfaction at SMA IT Fithrah Insani West Bandung both simultaneously and partially. This study applies a quantitative approach. Respondents in this study were 37 people who were adjusted to the characteristics of respondents at SMA IT Fithrah Insani West Bandung. The data collection method used was a questionnaire with a research measurement scale using semantic differential. The data processing technique used was descriptive and associative analysis. The method used was multiple linear regression and determination with the SPSS version 26 program tool. The results of this study explain that work discipline has a positive influence on job satisfaction as well as communication. In addition, work discipline and communication simultaneously affect the job satisfaction of Permanent Teachers of the Foundation at SMA IT Fithrah Insani West Bandung. Keywords: Work Discipline, Communication, Job Satisfaction